CP 2021
DOI: 10.12788/cp.0090
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and the risk of homicide-suicide among older adults

Abstract: Identify patients who are at risk, and implement measures to protect them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Michelle Carter, who was 17 at the time of Roy’s death, was charged with involuntary manslaughter after text messages were found that appeared to show her encouraging Roy to kill himself. During the subsequent bench trial, the defense called upon both a forensic electronics expert and a psychiatrist 48 . The digital material admitted as evidence in this case included hundreds of text messages between the defendant and the decedent, multiple social media posts, and also text messages sent by Carter to individuals other than Roy.…”
Section: Privacy and Ethical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Michelle Carter, who was 17 at the time of Roy’s death, was charged with involuntary manslaughter after text messages were found that appeared to show her encouraging Roy to kill himself. During the subsequent bench trial, the defense called upon both a forensic electronics expert and a psychiatrist 48 . The digital material admitted as evidence in this case included hundreds of text messages between the defendant and the decedent, multiple social media posts, and also text messages sent by Carter to individuals other than Roy.…”
Section: Privacy and Ethical Considerationsmentioning
confidence: 99%
“…The defense argued that Carter and Roy each suffered from mental illness and that Carter was not the cause of Roy’s actions, in support of which they also cited various digital materials that Carter and Roy had both created. The psychiatrist who testified as expert in the case opined that Carter suffered from a mental illness at the time of Roy’s death and that this illness had substantially impaired her judgment 48 . The judge did not agree with that opinion and found Carter guilty of involuntary manslaughter.…”
Section: Privacy and Ethical Considerationsmentioning
confidence: 99%